Association of common thrombophilias and antiphospholipid antibodies with success rate of in vitro fertilisation - Steinvil, Arie; Raz, Raanan; Berliner, Shlomo; Steinberg, David M.; Zeltser, David; Levran, David; Shimron, Orit; Sella, Tal; Chodick, Gabriel; Shalev, Varda; Salomon, Ophira (Thrombosis and Haemostasis, 2012)
Assisted reproductive technology (ART) is extensively used as a tool for pregnancy achievement in subfertile couples. Congenital and acquired thrombophilias have been suggested by some investigators to play a role in abnormal embryo implantation and placentation. The objective of this study was to assess the role of common thrombophilias in women with unexplained infertility undergoing in vitrofertilisation (IVF). We retrospectively analysed 594 women from a large healthcare maintenance organisation going through IVF and who had a thrombophilia workup, and compared them for prevalence of thrombophilia to two reference groups consisting of 637 fertile women from previous work and 17,337 women members of the same healthcare organisation with no history of venous thromboembolism. The mean age of the women at the first cycle of IVF was 30.9 years (SD: 4.1).The mean number of IVF cycles was 7.3 (SD: 5.0), and the mean fertility success rate per woman was 14.6% (SD: 19.0%). None of the common thrombophilias tested was found to be significantly associated with the number of IVF cycles or with lower fertility success rate. Rather, women who had APCR and /or factor V Leiden and lupus anticoagulant had significantly higher live birth rates (12.3% and 12.6%, respectively) in comparison to women who were tested negative (9.0% and 9.7%, respectively). Thus, hypercoagulability is not associated with failure to achieve pregnancy. These data suggest that neither screening for thrombophilia nor anticoagulant treatment is indicated in cases with unexplained reproductive failure.
Keywords: Thrombophilia; IVF; factor V Leiden; APCR; antiphospholipid antibodies